Effect of grain size on corrosion behavior of 304 stainless steel in coal chemical high salty wastewater. (March 2023) - Yang, Guangming; Du, Yafei; Chen, Siyao; Ren, Yongsheng
Abstract: Effects of microstructural evolution on the semiconducting properties and pitting behavior of 304stainless steel were studied by electrochemical measurement. These results showed that the grain coarsening reduces the corrosion resistance of 304 SS in coal chemical high salty wastewater (CCHSW), due to the larger high-angle grain boundary fraction promoting the defects formation in passive film. The higher donor density on the surface of the specimen deteriorated passive film stability. In addition, the lifetime, growth rate, and peak current of metastable pits increase with grain coarsening. Moreover, the width-depth ratio of stable pits increases gradually, and changes the shape of stable pits. Graphical Abstract: ga1 Highlights: Pitting corrosion analysis of 304 SS in CCHSW was investigated. The concentration of defects in passive film increases with the increased grain size. Coarse-grained could drastically extend the lifetime of metastable pits. Cl - and SO4 2- absorption in pits/matrix interface caused the pit fracture.